(untitled) (LACCEI, 2024)
Mass landslides occur mainly due to water saturation in the different soil strata of a slope, being the rainy season (December-April) the time when they are activated and produce more landslides. Such is the case of study of the present article which is referred to the so-called landslide 1 located in the Huancavelica region - Peru. In addition, thanks to the geotechnical and geophysical studies it was determined that the slope has a fractured rocky basement, this causes the water to infiltrate and flow faster through the fractures, causing a rapid saturation in the lower part (discharge zone), generating an increase in pore pressure causing the stability condition to be reduced and the slope to fail. In order to reduce the interstitial water level, horizontal drains have been implemented, whose function will be to channel and evacuate the flow of infiltrated water within the geological masses. For this purpose, modeling was carried out in SLIDE software. The results obtained showed that the slope improves its stability with the inclusion of horizontal drains, having a safety value of 1.305 without drains and 1.512 with horizontal drains. We can conclude that the technique of including horizontal drains to improve slope stability is efficient for establishing landslide prevention and control measures.